ENVIRONMENTAL PERCEPTIONS OF CHILDREN AND TEENAGERS FROM VILLA PEHUENIA, NEUQUÉN - Miguel Angel Prieto; Luciano Javier Sánchez; María Cecilia Navarro; Adela Maria Bernardis (Boletín Geográfico)
The present work makes reference to the characterization of the environmental problems of Villa Pehuenia, Neuquén province, through mappings that reflect the perceptions of specific population groups: children and adolescents. The methodology used was that provided by social cartography, which is based on a participatory spirit of the social actors involved. For the realization of this, we worked with students and teachers of Primary school N° 90 and the Secondary school Cristiana de la Villa. The methodology used is based on the conceptual foundations of participatory research and action which is a way of approaching social problems, diagnosing them and looking for ways to formulate a proposal for change in social reality without leaving aside the implication of parts. The collective elaboration of maps integrates the knowledge, the knowledge of all, propitiating an approach of the community to its geographical environmental space. Finally, each group presented their map and created the appropriate environment to hold a debate on the work done. In a second stage, a systematization of the data and subsequent preparation of a map per school that characterizes the city was carried out. From the results obtained, it is highlighted that the biggest environmental problem identified is the presence of loose dogs, pollution in general, clandestine dumps and deforestation.